2021
DOI: 10.1038/s41598-020-79529-y
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin administration provokes the activity of dendritic reticular cells in the seminal vesicle of Soay ram during the non-breeding season

Abstract: Dendritic cells (DCs) are innate immune cells which engulf, process and present antigens to the naïve T-lymphocyte cells. However, little is known about the effect of melatonin on the DCs. The present study aimed to investigate the morphology and distribution of the DCs by transmission electron microscopy and Immunohistochemistry after melatonin administration. A total of 8 out of 15 adult ram was randomly selected to receive the melatonin implant and the remaining 7 animals received melatonin free implants. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 79 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…open image with CMEIAS Color Segmentation, then select "Process" from the menu items and subsequently choose "Negative image" (Gross, Reddy, & Dazzo, 2010). This program was used by some authors (Abd-Elhafeez, Abou-Elhamd, Abdo, & Soliman, 2020; Abd-Elhafeez, Abou-Elhamd, & Soliman, 2020; Abd-Elhafeez, Hassan, & Hussein, 2021).…”
Section: Digital Coloring Of Scanning and Transmission Electron Microscopic Imagesmentioning
confidence: 99%
“…open image with CMEIAS Color Segmentation, then select "Process" from the menu items and subsequently choose "Negative image" (Gross, Reddy, & Dazzo, 2010). This program was used by some authors (Abd-Elhafeez, Abou-Elhamd, Abdo, & Soliman, 2020; Abd-Elhafeez, Abou-Elhamd, & Soliman, 2020; Abd-Elhafeez, Hassan, & Hussein, 2021).…”
Section: Digital Coloring Of Scanning and Transmission Electron Microscopic Imagesmentioning
confidence: 99%
“…Negative images were performed by using CMEIAS Color Segmentation, which is a free, improved computing technology. This has been done by the following steps: open image with CMEIAS Color Segmentation, then select “Process” from the menu items and subsequently choose “Negative image" (Gross et al, 2010; Abdel-Hakeem et al, 2019; Mustafa, 2019; Soliman et al, 2020; Abd-Elhafeez et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it was demonstrated that SARS-CoV-2 receptor binding domain (RBD) binds to bat angiotensin-converting enzyme 2 (ACE2) with lower affinity than to human ACE2 [ 33 ]. On the other hand, it has been recently shown that melatonin administration stimulates the activity of dendritic reticular cells and macrophages through increasing the size, number, and endosomal compartments which may correlate to increased immunity; melatonin activates the proliferation and maturation of all immune cells including T and B lymphocytes, granulocytes, and monocytes [ 34 ]. Based on these data we can speculate that the high levels of this molecule can be beneficial for antiviral immunity.…”
Section: “Bat-coronavirus-resistance” Hypothesis Of Melatonin Benefitsmentioning
confidence: 99%
“…Animal studies Stimulates dendritic cells and macrophages 1 g (subcutaneous implant) [34] Decreases the levels of IL-6, TNF-α, leptin 1 mg/kg [55] Inhibits the activation of the NLRP3 inflammasome; reduces the level of IL-1β 30 mg/kg [65] Inhibits NF-κβ and down-regulates MMP-3 3 mg/kg [66,67] Reduces the levels of Hsp70e, CRP, IL-6 and TNF-α 200 mg/kg [68] Decreases oxidative stress after lung irradiation by enhancing the regulation of catalase, superoxide dismutase, glutathione, NADPH-oxidase 2 and 4, and by reducing the level of malondialdehyde 100-200 mg/kg [75] Reduces bleomycin-induced experimental lung fibrosis and decreases transforming growth factor-β1-induced fibrogenesis in lung fibroblasts 5 mg/kg [76] No lethality was observed 800 mg/kg […”
Section: Effects Of Melatonin Dose Referencesmentioning
confidence: 99%